[DesktopLabs] Desktop Laboratories: Web Share and Additive Manufacture of Engineering Educational Models. (2015) - Leary, Martin; Mazur, Maciej; McMillan, Matthew; Brandt, Milan; Subic, Aleksandar
Abstract: Physical models are desirable in engineering education as they enhance visual literacy, provide insight into critical design failure modes and design attributes, and can be implemented in a classroom scenario in concert with multimedia displays and lecture slides. Despite the advantage, such physical models are often: not commercially available; are excessively costly; are not tailored to the intended learning outcomes; or are difficult to share across multiple geographic locations. In this work, the authors have developed an approach to address these shortcomings by exploiting the emerging capabilities of additive manufacturing equipment, increasingly present within educational institutions. The [DesktopLabs] project engages students to develop and additively manufacture physical models, to allow in-class demonstration of complex systems that would not be otherwise possible. By engaging with physical models of technical systems, students enhance their capacity to engage with emerging engineering technologies, and to solve new and complex problems. Combined with access to online sharing facilities, [DesktopLabs] allow web share of the developed model files, thereby allowing ready dissemination amongst other educators for additive manufacture in other geographic locations. Although applied in an engineering context, the benefit of [DesktopLabs] are directly transferrable to teaching areas to aid in the education of successive generations of undergraduate and postgraduate students.